Simulation of Rubber Friction Using Viscoelastic Behavior of Rubber and Roughness Parameters of Surfaces - Mohammad Reza Arab Bafrani; Mehdi Razzaghi-Kashani (علوم و تکنولوژی پلیمر, 2013)
One of the most important factors that affect tire friction is surface roughness, which determines the size of the real contact area, real pressure distribution on the contact interface, and scales of mechanical engagement between viscoelastic rubber and a rough substrate. The need to predict coefficient of friction (COF) for rubber on rough surfaces for applications such as traction of tires on the road surfaces led to some physical models such as Heinrich-Kluppel’s model. The current study examines the applicability of the Heinrich-Kluppel model, using different viscoelastic representations, in numerical simulations of COF for rubber, and its agreement with the experimental results. For this purpose, roughness characteristics of the surfaces and viscoelastic properties of rubber were measured by fractal analysis and dynamic-mechanical-thermal analysis (DMTA), respectively. These data were employed in the numerical code to simulate COF for a rubber sample. The model was also modified by replacing the Zener viscoelastic representation in the original model with the generalized Maxwell viscoelastic representation. On the other hand, COF for rubber was measured on the same rough surface (different sand-papers) by an in-house friction tester, and results were compared with the numerical results. It was shown that computer simulation could predict the load and speed dependence of rubber friction very well. The application of the generalized Maxwell model improved agreement between the numerical and experimental results for high sliding speeds where the Zener viscoelastic model failed to predict the right trend in variation of COF with speed. This speed range was matched with the sliding velocities in the footprint of tire under rolling conditions.